Event study on China H&A cross-listed companies : the impact of A-share listings on the H-share companies' market performance - Zeng, Jupeng (2008)
Our event study results show that the H&A cross-listings have strong positive influence on the H shares’ market performance surrounding the A share listing period. Various domestic and foreign market factors and investor sentiments may explain this positive impact.